2009
DOI: 10.3357/asem.2566.2009
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Suppression Using Oral Contraceptives: Survey of Deployed Female Aviation Personnel

Abstract: The use of continuous OCPs is low in deployed women with aviation-related duties, yet a majority desires menstrual suppression. Continuous OCP use in this setting is associated with significantly improved compliance and significant reductions in specific menstrual burdens. Entry-level education is desirable and may reduce barriers to continuous OCP use by addressing risks, side effects, and daily pill adherence strategies. Flight surgeons should provide further education and consider continuous OCP dosing in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…However, 57% of the health professionals interviewed in a US-based study reported that their patients do not ask about the continuous use of COCs [18]. A survey of female US Army aviation personnel reported that 66% of the women desired the suppression of menstruation for deployment; however, only 16% used COCs continuously [19]. Among those women who did not use COCs continuously, 35% had insufficient knowledge about menstrual suppression [19].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, 57% of the health professionals interviewed in a US-based study reported that their patients do not ask about the continuous use of COCs [18]. A survey of female US Army aviation personnel reported that 66% of the women desired the suppression of menstruation for deployment; however, only 16% used COCs continuously [19]. Among those women who did not use COCs continuously, 35% had insufficient knowledge about menstrual suppression [19].…”
Section: Discussionmentioning
confidence: 94%
“…A survey of female US Army aviation personnel reported that 66% of the women desired the suppression of menstruation for deployment; however, only 16% used COCs continuously [19]. Among those women who did not use COCs continuously, 35% had insufficient knowledge about menstrual suppression [19]. Another survey of female military personnel [20] showed that 66% desired menstrual suppression, although only 21% used COCs continuously [21].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent military studies have shown continuous COC usage is only 15% in aviation personnel, despite operationally relevant benefits associated with its use. 13 Military women desired to use menstrual suppression as an alternative to experiencing menstruation during deployment. 14 Many women desired suppression for deployment (66%) but only 21% continuously used COCs.…”
Section: Menstrual Suppression Methods For Astronautsmentioning
confidence: 99%
“…Therefore, suppression of menses is desirable/ favorable. Thus far, the impact of menstrual suppression has been studied in several countries for various reasons (5,6). …”
Section: Introductionmentioning
confidence: 99%